2021
DOI: 10.3390/plants10081597
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cultivating Tobacco and Supplying Nitrogenous Fertilizers on Micronutrients Extractability in Loamy Sand and Sandy Soils

Abstract: This research was conducted to evaluate the trends of the extractable micronutrients boron (B), copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn) in soils differing in textures and collected before tobacco cultivation, and in after unfertilized and fertilized (N10P18K24 and CAN 27%) plots. The soils and tobacco leaves were assessed on the contents of the micronutrients after unfertilized and fertilized tobacco cultivation. In soils, tobacco cultivation with fertilization increased the extractable Cu, Fe, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The correlation matrix revealed a moderately positive relationship between 232 Th and the soil sand fraction, and a moderately negative relationship with electrical conductivity, silt and clay fractions in soil, and an extremely weak relationship with soil pH. Thus, a strong positive correlation of 238 U with sandy soils could also reflect the ability of tobacco plant preference in sandy soils (Lisuma et al 2020 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation matrix revealed a moderately positive relationship between 232 Th and the soil sand fraction, and a moderately negative relationship with electrical conductivity, silt and clay fractions in soil, and an extremely weak relationship with soil pH. Thus, a strong positive correlation of 238 U with sandy soils could also reflect the ability of tobacco plant preference in sandy soils (Lisuma et al 2020 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The twist in irrigation water requirement resulted in different status of macronutrients, micronutrients, and other leaf parameters of Alfalfa (M. sativa) (Elfanssi et al, 2018). Thus, in line with the increase of micronutrients due to fertilization that Source: Authors provided an insight into the positive relationship between nutrients and the applied fertilizer (Lisuma et al, 2021), trace elements responded to the soil amendment.…”
Section: Resultsmentioning
confidence: 98%
“…To further clarify the effect of B on the growth and development of flue-cured tobacco seedlings, the correlation analysis of all involved indexes showed that there was a significant negative correlation between B accumulation and nicotine content in each part of flue-cured tobacco, confirming that B may influence nicotine synthesis and accumulation [52,53]. As a result, the rational use of B fertilizer can regulate the nicotine content.…”
Section: Interactions Between Indices To Different B Solution Concent...mentioning
confidence: 98%